Analisis Service Quality Dan Corporate Image Dalam Meningkatkan Customer Satisfaction PT Bank Pembangunan Daerah Jawa Timur,Tbk Cabang Kediri - Sari, Lina Puspita (Otonomi, 2021)
A Bank is a financial institution that accepts deposits from the public and creates a demand  deposit while simultan areousky giving loans. Banking is business that deponds on trust, there fore service quality and reputation determine success in business. The aim of this research is to analyse the effect of service quality and corporate image towards customer satisfaction in Bank Jatim Kediri branch.This research placed in Bank Jatim Kediru branch with 70 respondent sample site. The independent variable ( X ) were service quality, corporate image, whilst the dependent variable ( Y ) was customer satisfaction. Accidental random sampling was applied.This research showed that, there was significant correlation between service quality and corporate image towards customer satisfaction in Bank Jatim Kediri branch. The result of this research suggested that Bank Jatim employees. Should increase their standard of in customer service and give excellent impression to of corporate image so that customer loyalty can be established